До питання про теоретичні засади дослідження комунікативної поведінки депресивної особистості - Карпіна, Олена Олександрівна; Karpina O. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано теоретичні засади дослідження комунікативної поведінки депресивної особис¬тості. Висвітлено погляди на депресію, характерні для історичного періоду Середньовіччя та Відродження. Проаналізовано домінуючі терміни на позначення поняття «депресія», такі як «меланхолія», «акедія», «тріс¬тітіа», «сплін», «енюі» тощо. Розглянуто основні моделі поведінки депресивної особистості часів Середньо¬віччя та Відродження. The article examines the theoretical principles of communicative behavior of depressive personality. The attention is focused on the historical period of the Middle Ages and the Renaissance. The dominant terms of the notion «depression», such as «melancholy», «acedia», «tristitia», «spleen» and «ennui» were described and analysed. The basic behavior patterns of depressive personality of the Middle Ages and the Renaissance were pointed out. The article presents the views of scientists and clinicians who investigated the specific behavior of people with the symptoms of depression. The transformation of the complex and multifaceted phenomenon was traced during this investigation: if the Middle Ages melancholy was characterized by inherent aggressive outbursts, during the Renaissance this phenomenon acquired a certain finesse and was marked by fatigue and indifference, thereby referring aggressive manifestations to the category of mental deviations, thus remaining within the framework of decency.
On the Theoretical Foundations of the Study of Communicative Behavior of Depressive Personality
Keywords: меланхолія; melancholy; акедія; acedia; депресія; depression